Archive of the Church of Catalonia during the Spanish Civil War, I: July to december 1936, Edition prepared by Hilari Raguer i Suñer - Álvarez Bolado, SJ, Alfonso (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
This article reviews extensively the first volume, by Hilari Raguer, of the critical edition of Arxiu de l’Església catalana durant la Guerra Civil (Archive of the Church of Catalonia during the Spanish Civil War). This work will gather the correspondence between Catalonian bishops and the Holy See, or between the same bishops and the general vicars of Catalonian dioceses, together with related documents. The sources of this documentation are the Archivo Vidal i Barraquer (archbishop of Tarragona from 1919 to1943 —where he never came back to after the end of the War— and cardenal since 1921), the Archivo Guitart (Bishop of Seu d’Urgell and coprince of Andorra), the Archivo de Josep M. Torrent i Lloveras (who was General Vicar in Barcelona and maintained an important correspondence with the Secretary of State of the Vatican and the authorities of the Spanish Republic), the Archivo de Salvador Rial (appointed by Vidal i Barraquer as General Vicar of Tarragona). This first volume, which covers the first six months of the Spanish Civil War, focuses on several main topics: how the bishops explained their respective flight to Andorra, France, Italy and, afterwards, to the zones controlled by General Franco; the religious persecution in Catalonia after the failure of the military coup, and the anxiety for the fate of the other bishops, priests and prominent lay people; the course of the Civil War and the bishop’s longing for the victory of the «good ones» (the insurrectionists), which they took for granted or most probable; the Discourse of Pope Pious XI in Castelgandonfo on September 14th and its various interpretations, both among exiled people and within the divided Spain; the tense atmosphere in Rome, especially because of some extreme conservative lay catholics; the opportunity of adressing a congratulatory message to General Franco in case he would conquer Madrid; the situation of the Church and the different church collections raised by Gomà and Vidal i Barraquer; the hospitality of fleeing priests and their accommodation in various dioceses or their relocation in the Spain of General Franco.